IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 53 TAHUN 2010 TERKAIT DISIPLIN PEGAWAI NEGERI SIPIL DALAM RANGKA MENINGKATKAN KINERJA PEGAWAI NEGERI SIPIL DI PEMERINTAH KOTA YOGYAKARTA - , Ika Untari, SH; , Dwi Haryati, S.H, M.H, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to determine the implementation of government regulation number 53 of 2010 on the 3 discipline of civil servants towards improved performance, knowing the effort to reduce the occurrence of violations of discipline by the civil service by civil servants' After the enactment of government regulation number 53 of 2010. This study is a combination of empirical research conducted by identifying and clarifying the implementation of the provisions of the legislation (field), and a normative study that examines the various provisions of laws and legislation related to the discipline of civil servants (literature). This research will tobe processed using qualitative descriptive methods. The results of the study show that: 1. Implementation of Government Regulation No. 53 of 2010 concerning the discipline of civil servants on performance improvement in Yogyakarta City Government already applied with discipline, using the DP3 and Employee Performance Assessment Tool. 2. Constraints faced Implementation Government Regulation No. 53 of 2010 is the direct supervisor or the competent authorities do not fully understand the procedures of Government Regulation No. 53 of 2010 in terms of the application of how to perform the examination, because there is a hierarchy in PP 53 personnel. 3. Efforts are made to reduce the occurrence of breach of discipline is the Regional Employment Board of Yogyakarta to guide employees, increase understanding of Government Regulation No. 53 of 2010 in the City of Yogyakarta.